ISLAM NUSANTARA DAN ISLAM DI NUSANTARA: PERKEMBANGAN ISLAM SEJAK MASUKNYA SAMPAI KINI - Samuel Charlies Mowoka (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2020)
Almost everyone recognizes that within him there is a greater force outside himself. That Power is called by various terms including themost common one is God, Dewa, Puang Matua (in Toraja), Tete Manis (in Ambon), Sang Hyang Widi and so forth. All of that shows the recognition of something that has the power and power that governs everything outside of humans (“The Supreme Beings”). Indonesia`s population is the highest Muslim religion in the world. Seeing this statement, the question that arises is “why?, what is the appeal of Islam to have lage following in Indonesia?”. To find this out, we must look at the whole starting from the history of the Indonesia, Islam’s entry into Indoensia, and its development. If you look at the history of Indonesia before Islam entered, this country is not the middle of nowhere empty, without inhabitants, and without trust. Therefore, the presence of Islam in Indonesia must experience a meeting with the beliefs of the first Hindu and Buddhist religions. This is interesting upto Islam entered into a religion that has most followers not only in Indonesia but also in the world.